2007
DOI: 10.1073/pnas.0609229104
|View full text |Cite
|
Sign up to set email alerts
|

Structures and spectral signatures of protonated water networks in bacteriorhodopsin

Abstract: Networks of internal water molecules are thought to provide proton transfer pathways in many enzymatic and photosynthetic reactions. Extremely broad absorption continua observed in recent IR spectroscopic measurements on the photodriven proton pump bacteriorhodopsin (BR) suggest such networks may also serve as proton storage and release sites for these reactions. By combining electronic structure calculations with molecular mechanical force fields, we examine the dynamics and the resulting IR spectra of two pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
144
0
3

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 55 publications
5
144
0
3
Order By: Relevance
“…The continuum electrostatics calculations, however, were based on simple point-charge models and therefore are not conclusive; the close distances between Glu-194, Glu-204 and the relevant water molecules indicate that a quantum mechanical treatment of these residues is warranted for a quantitative consideration of the protonation pattern in this region. CarParrinello molecular dynamics (CPMD)-based quantum mechanical/molecular mechanical (QM/MM) simulations (6) found that a protonated water cluster in the PRG region generated a continuum IR band qualitatively consistent with the experimental observation, providing further support to the idea of involving water clusters rather than amino acid side chains as the proton storage site. However, the QM region included only the protonated water molecules and therefore did not allow proton transfer to the Glu residues.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The continuum electrostatics calculations, however, were based on simple point-charge models and therefore are not conclusive; the close distances between Glu-194, Glu-204 and the relevant water molecules indicate that a quantum mechanical treatment of these residues is warranted for a quantitative consideration of the protonation pattern in this region. CarParrinello molecular dynamics (CPMD)-based quantum mechanical/molecular mechanical (QM/MM) simulations (6) found that a protonated water cluster in the PRG region generated a continuum IR band qualitatively consistent with the experimental observation, providing further support to the idea of involving water clusters rather than amino acid side chains as the proton storage site. However, the QM region included only the protonated water molecules and therefore did not allow proton transfer to the Glu residues.…”
supporting
confidence: 60%
“…Another important mechanistic issue concerns the identity of proton storage site(s), which is difficult to determine unambiguously because protons are invisible in the crystal structure of most biomolecules. Indeed, although titratable amino acids are the common suspect for proton storage sites, the unconventional possibility of storing proton in water clusters has also been raised in several recent studies (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Although water molecules are well known to transiently facilitate proton transfers in many different settings, recent Fourier-transform infrared studies found evidence for the existence of long-lived protonated water cluster as the "proton storage site" in bacteriorhodopsin; 8,9 the interpretation seems to be supported by computational studies. 9,10 Recent simulation study of Xu et al also raised a similar possibility in cytochrome c oxidase. 11 To thoroughly examine these proposals, it is imperative to be able to compute reliable IR spectra for water clusters in different protonation states in a biomolecular environment.…”
Section: Introductionmentioning
confidence: 84%
“…The computational efficiency of SCC-DFTB makes it, in principle, an attractive choice in this context and complementary to calculations based on much more expensive QM methods that might suffer from convergence issues. 10 Although previous studies based on NMA indicate that SCC-DFTB overall gives favorable vibrational frequencies among semiempirical methods, 28,29 whether it is capable of capturing the spectroscopic signatures of various water clusters remains unknown. In this study, we carry out SCC-DFTB calculations for the IR spectra of various protonated water clusters in the gas phase and compare the results to experimental spectra, which only became available very recently.…”
Section: ͑4͒mentioning
confidence: 99%
See 1 more Smart Citation